PEMETAAN..KARAKTERISTIK..IKLIM..GELOMBANG..DI.. INDONESIA - Medyna Ramsya, Arsent
Most of the Indonesian territory is covered by water. This causes many Indonesian people do economic activities in waters, such as shipping and construction. These activities have an important role in improving Indonesia economy. However, these activities can be affected by several factors, one of them is the existence of sea waves that affect these economic activites. In this final project research, the author will make a map of wave climate characteristics in Indonesia which can be used as a reference in policy making by agencies related to shipping and construction to ensure the safety of these activities, so it can reduce losses and improve Indonesian economy. The research method that author use is conducting wave climate modeling in Indonesian waters from bathymetry data and wind data in Indonesian waters during 25 years using SWAN software version 41.20, then presenting it in the form of a wave climate map in Indonesian waters. The results showed that significant wave height range between 0-2.5 meters, while wave period range between 0-6 seconds. Waves characteristics in Indonesian waters vary spatially due to differences of water area. Other than that, the author also specify several observation points to find out wave characteristics in every waters in Indonesia. The results showed that every observation point experiences maximum wave at different times. Waters in the northern Indonesia experience maximum wave around December-February, while waters in the southern Indonesia experience maximum wave around June-August. Maximum monthly average of significant wave height is 1.358 meters, occurred in the Arafura Sea in June. Maximum monthly average of wave period is 5.523 seconds, occurred in the Pacific Ocean in February. These waves vary temporally due to seasonal monsoons.